Wytwarzanie przestrzeni autentycznej jako krytyka nowoczesności - Schudy, Hanna (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
The paper discusses social practices of creating as well as producing authentic objects and space. My deliberations are based on the thesis of the authors of the books The tourist gaze (John Urry), The tourist. A new theory of the leisure class (Dean MacCannell); Contested natures (Phil Macnaghten and John Urry), but also on my own research concerning attitudes towards wolfs in western and eastern Poland. The point of the article is that at the age of the new visual media, postmodernism and posttourism, when it is difficult to recognize whether an object is the original or a copy, man still wants to stand on the firm ground of genuine values. The sociologists mentioned above claim that this is why in the modern world there is a demand for authentic objects and so in an answer to this need such attractions like w i l d n e s s and r u s t i c i t y are produced. In the first part of the article I present an example of a visual product – an English cottage. Secondly, basing on the results of some research concerning attitudes towards wolves, I attempt to show that in Poland there are also some practices the idea of which is to create an authentic space - wild nature. Finally I emphasize that constructed authentic space, scenes, and landscapes are examples of myths – wildness, rusticity – the consequence of nostalgia for lost authentic world.
Creating authentic space as a critique of modernity
Keywords: natura; nature; kracja; creation; mit; myth; sakralizacja; sacralization; obiekt wizualny; visual objects; atrakcja; attraction